2014
DOI: 10.3389/fpubh.2014.00103
|View full text |Cite
|
Sign up to set email alerts
|

Current Perspectives on Viable but Non-Culturable (VBNC) Pathogenic Bacteria

Abstract: Under stress conditions, many species of bacteria enter into starvation mode of metabolism or a physiologically viable but non-culturable (VBNC) state. Several human pathogenic bacteria have been reported to enter into the VBNC state under these conditions. The pathogenic VBNC bacteria cannot be grown using conventional culture media, although they continue to retain their viability and express their virulence. Though there have been debates on the VBNC concept in the past, several molecular studies have shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
263
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 357 publications
(271 citation statements)
references
References 100 publications
3
263
0
5
Order By: Relevance
“…For these reasons it is difficult to correlate the two approaches although this is commonly done due to a lack of a practical alternative standard reference method [9,12,16]. There is a growing body of evidence pointing to the virulence of VBNC bacteria and suggesting the importance of measuring their numbers in environmental waters [17][18][19]. For this purpose enzyme assays are a measurement technology which could be implemented and optimised.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons it is difficult to correlate the two approaches although this is commonly done due to a lack of a practical alternative standard reference method [9,12,16]. There is a growing body of evidence pointing to the virulence of VBNC bacteria and suggesting the importance of measuring their numbers in environmental waters [17][18][19]. For this purpose enzyme assays are a measurement technology which could be implemented and optimised.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of VBNC L. pneumophila in water distribution systems may lead to false confidence that the bacteria have been eradicated from the system if presence is determined by a culture method. In other species of bacteria, it has been shown that gene expression can be altered in the VBNC state, typically showing gene supression [129]. However, it has been shown that VBNC cells retain intact genetic material and there are no genetic knockdowns during the VBNC state [130,131].…”
Section: Effects Of Engineered System Stressors On L Pneumophilamentioning
confidence: 99%
“…Pure culture method has also been used to detect pathogenic microorganisms. However, a large number of microorganisms and pathogens cannot be detected by pure culture because although they are viable, they are non-culturable [8]. In addition, water-borne microorganisms are characterized by low abundance, diversity, and complexity, which make them difficult to detect.…”
Section: Introductionmentioning
confidence: 99%